Social Support and Quality of Life in School-Aged Children with Thalassemia Major - Murtilita, Murtilita; Mediani, Henny Suzana; Mardiah, Wiwi; Saifudin, I Made Moh. Yanuar (Indonesian Journal of Global Health Research, 2024)
Social support is essential in improving the quality of life for children with thalassemia major. This study aims to examine the relationship between social support and the quality of life of school-aged children with thalassemia major. Methods:This cross-sectional study involved 82 children aged 8-12 years with thalassemia major at Garut District Hospital’s Thalassemia Clinic. Data were collected using the Child and Adolescent Social Support Scale (CASSS) and the Pediatric Quality of Life Inventory (PedsQL) 4.0. Pearson correlation and linear regression analyses were used to explore the relationships between social support and quality of life. Results: The study found a significant positive relationship between total social support and the quality of life of children with thalassemia major (r = 0.388, p < 0.001). Among the different types of support, close friend support showed the strongest correlation with quality of life (r = 0.405, p < 0.001). Conclusion: Social support, particularly from close friends, plays a crucial role in enhancing the quality of life of school-aged children with thalassemia major. Close friend support was the most influential factor, followed by parental and teacher support. These findings highlight the importance of emotional and social support in managing chronic illnesses in children.